The Effect of Leadership and Management Training in Nursing BasedMedeline Leininger Theory Regarding the Implementation of Managerial Functions of Room Heads with Executives - Ta'dung, Selvyana (Syntax Corporation Indonesia, 2024)
This research identifies the characteristics of respondents and eval_uates the impact of training on the implementation of managerial functions at the Lukas Enembe Hospital - Central Memberamo. Findings show that the majority of respondents in the treatment group were women (70.0%) and the majority were under 30 years old or between 30-40 years old. In contrast, the control group was dominated by women (65.0%) and most were aged 30-40 years. In terms of work experience, the treatment group tended to have work experience of ≤5 years, while the control group had work experience of >5-10 years. The implementation of management functions in the treatment group showed a significant improvement after training, with a decrease in the poor and moderate categories, and an increase in the good category. Statistical analysis with Asymp.Sig value. 0.000 indicates a significant effect of training. Recommendations include the implementation of ongoing training with follow-up sessions, the use of relevant case studies, regular eval_uations, as well as the integration of Leininger's theory in the educational curriculum and collaboration between educational institutions and RSUD. Researchers are advised to choose an appropriate research design and conduct in-depth data analysis to eval_uate the impact of training in a statistically significant way.